Facial synthesis of two-dimensional In2S3/Ti3C2Tx heterostructures with boosted photoactivity for the hydrogenation of nitroaromatic compounds. (5th August 2021) - Zhu, Yisong; Xie, Guanshun; Li, Guohao; Song, Fei; Yu, Changqiang; Wu, Zhenjun; Xie, Xiuqiang; Zhang, Nan
Abstract : In this work, Ti3 C2 T x  (MXene) acts as the platform for directing the growth of 2D In2 S3  nanoflakes, thereby generating 2D In2 S3 /Ti3 C2 T x  heterostructures, which exhibited boosted photocatalytic activities compared to bare In2 S3 . Abstract : Two-dimensional (2D) heterostructures have gained increased interest in recent years due to the integrated functionalities of the individual building blocks and beyond. Herein, we have fabricated 2D In2 S3 /Ti3 C2 T x heterostructures through a facile one-step low temperature refluxing method. While bare In2 S3 tends to evolve as nanoparticles, it is found that Ti3 C2 T x (MXene) acts as the platform for directing the growth of 2D In2 S3 nanoflakes, thereby generating 2D In2 S3 /Ti3 C2 T x heterostructures. For the probe reaction of nitroaromatic compound hydrogenation, In2 S3 /Ti3 C2 T x composites exhibited boosted photocatalytic activities compared to bare In2 S3, which can be ascribed to the favorable active site exposure in the 2D/2D heterostructures and the "electron sink" effect of the Ti3 C2 T x nanosheets. This work distinctly indicates that Ti3 C2 T x nanosheets are a promising platform for fabricating 2D/2D heterostructures for photoredox catalysis.